Ready for new business models? Human and social capital in the management of renewable energy cooperatives in Germany. (September 2021) - Herbes, Carsten; Rilling, Benedikt; Holstenkamp, Lars
Abstract: Policy makers in various countries have made the development of community energy, especially in the form of a renewable energy cooperative (REC), a goal of energy policy. Weaknesses in qualifications of REC management teams have been identified by previous research as a barrier for the further development of RECs, especially when implementation of new business models is needed. Our study is the first to examine in detail the qualifications (human capital) and networks (social capital) of REC management; our data comes from online survey responses from 187 board members of 125 RECs in Germany. We analyzed how many RECs are planning to implement new business models, finding that less than half of the surveyed RECs are planning to do so. Those REC boards that are planning new business models will require skills in sales and marketing, but REC management has qualification weaknesses and gaps in their networks precisely in these two areas. RECs could remedy these problems by bringing onboard new management team members with complementary qualifications and networks, partnering with other RECs and organizations, and training management team members. Policy makers committed to community energy can support RECs through training programs and assistance in building partnership networks. Highlights: New business models often require qualifications in marketing and sales. In Germany, cooperatives' management often shows gaps in these two areas. We worked with online survey responses from 125 cooperatives in Germany. RECs could qualify or complement their management or form partnerships. Policy makers can help in building partnerships and through training programs.